Interdisciplinary teambuilding in management research - Iryna Shavkun; Yana Dybchynska (Менеджмент та підприємництво: тренди розвитку)
The interdisciplinary approach in science, education and practice has acquired particular importance over the past decade, characterized by the rapid development of technological innovations, increasing uncertainty of the external environment and large-scale changes in the political, economic and social spheres.